Regulation of mitochondrial ribosomal protein S29 (MRPS29) expression by a 5'-upstream open reading frame - Han, Min-Joon (2010)
Mitochondrial ribosomal protein S29 (MRPS29) is a mitochondrial pro-apoptotic protein also known as death associated protein 3 (DAP3). Over-expression of MRPS29 has been reported to induce apoptosis in several different human cell lines while conferring resistance in glioma and Ataxia telangiectasia cells. These two contradictory reports led us to investigate the MRPS29-induced apoptosis further. Cyber searches of the EST databases revealed the presence of a splice variant of MRPS29 mRNA containing an upstream open reading frame (uORF) at the 5' untranslated region (UTR). In this study, we confirmed the presence of this uORF using real time RT-PCR and investigated its role in MRPS29 expression.